Investigação da imunomodulação por subpopulações de linfócitos na Leishmaniose visceral humana - Peixoto, Rephany Fonseca (2018)
Leishmaniasis is characterized as a complex of infectious-parasitic diseases caused by protozoa of the genus Leishmania. These diseases are present in 98 countries, where about 350 million people are at risk of infection. Visceral leishmaniasis (VL) is the most severe clinical form of the disease and induces immune responses mediated by distinct cell subpopulations, including invariant natural killer T cells (iNKT-CD3 + 6B11 +), regulatory T cells (Tregs - CD4 + CD25highFOXP3 +), which can be classified into natural Treg (CD4 + CD25highFOXP3 + CD45RA +) and memory Treg (CD4 + CD25highFOXP3 + CD45RA-). IL-10 is a key cytokine in the immunopathology of this disease and the mechanisms of action involved in the immunological modulation of human visceral leishmaniasis have not yet been well elucidated with respect to the subpopulations. Thus, our aim was to characterize iNKT and T regulatory cells (nTreg and mTreg) mechanisms during the diseases, and consequently evaluate the main cytokines produced. To achieve this goal, in the first part of this study, whole blood was collected from LV (n = 10) and uninfected (n = 7) patients, and the nTreg and mTreg subpopulations were evaluated with and without specific stimulation of the soluble antigen of Leishmania (SLA). The analysis of iNKT cells were also performed with and without specific stimulation of total Leishmania antigen (TLA) in whole blood samples in the LV (n = 12), nonendemic (CNE - n = 6) and in the endemic negative control group (CNegE - n = 6). All analyzes were performed by flow cytometry. Regarding the Tregs cells, the results demonstrated that: 1) A high number of memory Treg cells was observed when compared to the total number of natural Treg cells in all groups evaluated; 2) A significant reduction in CD39 / CD73 expression in mTreg cells was observed in the LV groups in the absence and / or presence of stimulus; 3) A decrease in CTLA-4 expression was observed in mTreg cells in the LV group in the absence of stimulation, when compared to the control group. However, SLA induced increased expression of CTLA-4 in patients with VL; 4) Significant changes in the production of IFN-? were not observed in any of the groups evaluated and 5) Low levels of IL-10 were observed in mTreg cells in the LV groups regardless of stimulus. In the iNKT cells, we observed that 6) the total ex vivo number of cells in the LV group did not change significantly in relation to the CNE and CNegE groups; 7) Regarding the recent activation profile of these cells, LV patients did not present significant changes in CD69 expression, as compared to the control groups both ex vivo and after culture in vitro (medium and TLA); 8) Following stimulation with L. infantum TLA, iNKT cells reduced IFN-? production. However, increased IFN-? production was observed in iNKT cells in the CNE group; 9) Regarding the production of IL-17, significant alterations were not observed, before or after TLA stimulation, in all the groups evaluated; 10) An increase in IL-10 production was observed in the CNE group when compared to CNegE and patients with VL independently stimulation. Thus, our results suggest that nTreg cells and iNKT cells, help maintain the effects of IL-10 on the chronicity of the disease. On the other hand, mTreg cells act counterbalancing the IL-10 mediated immunosuppression through mechanisms that aid in the induction of effector responses in the disease. However, despite the compensatory action of mTreg cells contributing to the establishment of VL control mechanisms, the pathogenic profile regulated by IL-10 still prevails in the disease.